ISOLATION AND DISEASE ASSESSMENT OF XANTHOMONAS ORYZAE PV. ORYZAE FROM JAVA ISLAND AND PATHOGENIC ASSAY ON NEAR ISOGENIC LINES WITH DIFFERENT RESISTANT GENES - ., Fatimah; Priyatno, TP.; Fadlillah, SH.; ., Hermanto; Baroya, M.; ., Mahrup; ., Wawan; Sasongko, D.; Suryadi, Y.; Kadir, TS. (JURNAL BIOLOGI INDONESIA, 2014)
Bacterial leaf blight disease caused by Xanthomonas oryzae pv oryzae (Xoo) is one of the important bacterial diseases,which is very destructive to rice plant. In this study, seventy isolates of Xoo were collected from several regions inWest Java, Central Java, Yogyakarta and East Java provinces and ten isolates from ICABIOGRAD collection. Theaim of the study was to survey variation and distribution of the pathogen and to study the interactions between theisolates and near isogenic lines carrying specific genes for bacterial leaf blight resistance. Twenty Xoo isolates wererandomly chosen to assess the differential characteristics of ten near-isogenic rice lines in Indonesia. The resultsshowed that xa5 resistant gene was the highest effective against the majority of Xoo isolate, followed by Xa21, andXa7 combined with Xa4 as the background. These findings are useful for rice breeding programs in designing stablebroad-spectrum bacterial blight resistant rice cultivars.Key words: Xanthomonas oryzae, resistant gene, Near isogenic line, Java